STRATEGI MENGANGKAT POTENSI UMKM LOKAL MELALUI PRODUKSI KERIPIK PISANG OLEH MAHASISWA KKN PMD UNRAM DI DESA LEBAH SEMPAGE KEC. NARMADA KABUPATEN LOMBOK BARAT - aditya, Anak agung surya; Kamila, Alya Zian; Parenty, Atika; Wijayanti, Arum; Fortuna, Gianta Arya Dwi; Febriansyah, Wandy; Hadi, Muhamad Rif’al; Alfiyanti, Isnaini; Agustina, Hardianti; Novita, Novita; Sabani, Rahmat (Jurnal Wicara, 2025)
Lebah Sempage Village has great potential in processing bananas into value-added products such as banana chips. However, this potential remains underutilized due to a lack of innovation, quality standards, and effective marketing strategies. The Community Empowerment Student Service Program (KKN PMD) of Mataram University aims to address these issues through training and mentoring local MSME (Micro, Small, and Medium Enterprises) entrepreneurs. The methods used include observation, production training, product innovation, packaging development, and digital and offline marketing strategies. The results of this program indicate an improvement in product quality, diversification of flavors, and an expanded marketing reach through social media and exhibitions. With this initiative, it is expected that MSMEs in Lebah Sempage Village can enhance their competitiveness and contribute to the welfare of the local community.